Parasite-Derived Proteins for the Treatment of Allergies and Autoimmune Diseases - Wu, Zhenyu; Wang, Lifu; Tang, Yanlai; Sun, Xi (Frontiers in Microbiology, 2017)
The morbidity of atopic diseases and disorders of immune dysregulation like asthma, food allergy, multiple sclerosis, atopic dermatitis, type Ⅰ diabetes mellitus, and inflammation bowel disease have been noticed increasing all around the world in the past decades. Though the roles of environmental factors and changes of genetic factors were particularly emphasized in etiopathology, they cannot exclusively explain the whole reason since they all need a long-term change. Epidemiological investigation has found that this increase also parallels with a decrease in infectious diseases especially the parasite infection. Thus, lowering prevalence of parasite infection may be another important reason for immune dysregulation . Parasites have co-evolved with the human immune system for a long time. Some immune-evasion molecules from parasites have been verified to reduce the incidence and harmfulness of atopic diseases by modulation the human immune responses. More important, some parasite-derived products are proved to inhibit the progression of inflammatory diseases and consequently alleviate the symptoms of inflammatory diseases. Thus, parasite especially their products may have potential applications in treatment of autoimmune diseases. In the review, therapeutic potential of the parasite-derived products and their analogues for the atopic diseases and immune dysregulation were summarized.